PROJECT BASED-LEARNING (PBL): AN OFFERED SOLUTION FOR SPEAKING CLASS - Hartatik, Sri Fatmaning (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
This Classroom Action Research (CAR) was intended to describe how Project Based Learning (PBL) could improve students’ speaking ability. This research was carried out to the fact that the students in one of private colleges in Malang faced some speaking problems such as anxiety and limited linguistic competence. The researcher believed that BPL could solve her teaching problem since some research as Permatasari (2013) and Maulany (2013) had come into conclusion that PBL could enhance students’ speaking skill and promote students’ collaborative skill. Following, the previous research, the findings of this particular research, which were revealed from various instruments, agree that PBL can provide optimum opportunity for the students to explore and practice speaking skill so that they can improve their speaking ability. Besides, the findings of the research show that this strategy had challenged the students to demonstrate their team –work ability.